2013
DOI: 10.1007/s00296-013-2687-2
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor (CAG)n polymorphism and androgen levels in women with systemic lupus erythematosus and healthy controls

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disorder that affects mainly females. Therefore, interrelations between the reproductive and immune system have been assumed. Considering the complex influence of hormones and receptors, we aimed to investigate the influence of androgens and androgen receptor (AR) polymorphism in women with SLE. One hundred and sixteen patients and 44 healthy women were investigated. Testosterone, sex hormone-binding globulin (SHBG), dehydroepiandrosterone-sulphate (DHEAS) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
12
0
2
Order By: Relevance
“…Conversely, females with lupus who had shorter AR exon 1 CAG repeats (which are associated with relatively amplified hormonal action) were found to have greater disease activity and more robust humoral autoimmune responses. Our current data are also similar to the observations in women with rheumatoid arthritis – in whom a shorter AR CAG repeat length was noted to be associated with earlier onset and more aggressive disease course (24) – and to a recent study of women with SLE in which the AR CAG repeat length was inversely correlated with the SLICC/ACR index of disease damage (25). Differences in androgen sensitivity conferred by AR CAG repeat variation in women do not appear to be compensated by alterations in circulating hormone levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, females with lupus who had shorter AR exon 1 CAG repeats (which are associated with relatively amplified hormonal action) were found to have greater disease activity and more robust humoral autoimmune responses. Our current data are also similar to the observations in women with rheumatoid arthritis – in whom a shorter AR CAG repeat length was noted to be associated with earlier onset and more aggressive disease course (24) – and to a recent study of women with SLE in which the AR CAG repeat length was inversely correlated with the SLICC/ACR index of disease damage (25). Differences in androgen sensitivity conferred by AR CAG repeat variation in women do not appear to be compensated by alterations in circulating hormone levels.…”
Section: Discussionsupporting
confidence: 90%
“…In humans, such variation in AR CAG repeat lengths has been found to be associated with phenotypic features of men with Klinefelter's syndrome (18), as well as with normal variation in facial and body hair (19), in body composition (20), in HDL levels (21), and in response to treatment with exogenous androgens (22). In a previous study, we found that longer AR CAG repeats were associated with more exuberant expression of IgG autoantibodies in males with lupus (23), while two recent reports have now identified inverse correlations between AR CAG repeat length and disease activity in women with rheumatoid arthritis (24) and lupus (25).…”
Section: Introductionmentioning
confidence: 88%
“…The minor allele A will significantly reduce the binding activity of the androgen receptor and then may result in the development of SLE. The androgen is important in clinical treatment of SLE [ 51 ] and the correlation between the androgen receptor and SLE has been investigated by different studies [ 52 , 53 ]. For other associated SNVs, we did not detect sufficient evidence and signals at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore investigated the effects of hormones, specifically E2, on the IFN-dependent and IFN-independent activation of cDCs from female and male lupus-prone mice. Different hormone receptor polymorphisms have been reported to modify SLE disease severity [ 46 ] and may affect different murine strains as well. Therefore, we investigated the effects of E2 and sex differences on cDC activation using TCSle mice [ 13 ] compared to its wild-type strain C67BL/6 (B6) to minimize possible differences in estrogen receptor signaling.…”
Section: Introductionmentioning
confidence: 99%